2020
DOI: 10.3390/biom10020240
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Reactive Oxygen Species in Arsenic Toxicity

Abstract: Arsenic poisoning is a global health problem. Chronic exposure to arsenic has been associated with the development of a wide range of diseases and health problems in humans. Arsenic exposure induces the generation of intracellular reactive oxygen species (ROS), which mediate multiple changes to cell behavior by altering signaling pathways and epigenetic modifications, or cause direct oxidative damage to molecules. Antioxidants with the potential to reduce ROS levels have been shown to ameliorate arsenic-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
111
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(139 citation statements)
references
References 241 publications
(262 reference statements)
4
111
0
Order By: Relevance
“…In addition, MDA levels increased significantly after As(III) poisoning, which indicated that the formation of peroxides was enhanced in response to toxicity. These results seem to be in agreement with the previous findings (Hu et al, 2020;Huo et al, 2020). However, UDCA promoted activity of SOD, CAT and GSH-Px and inhibited levels of MDA, ROS to the best level in hepatocytes, but it was still slightly lower than the Control.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, MDA levels increased significantly after As(III) poisoning, which indicated that the formation of peroxides was enhanced in response to toxicity. These results seem to be in agreement with the previous findings (Hu et al, 2020;Huo et al, 2020). However, UDCA promoted activity of SOD, CAT and GSH-Px and inhibited levels of MDA, ROS to the best level in hepatocytes, but it was still slightly lower than the Control.…”
Section: Discussionsupporting
confidence: 93%
“…
Figure 2 A simplified scheme depicting proinflammatory mechanisms of heavy metals. Briefly, heavy metal exposure results in increased ROS production and oxidative stress that latter may underlie heavy metal-induced activation of proinflammatory pathways NF-kB and MAPK with subsequent expression of target proinflammatory genes including cytokines, chemokines, enzymes, and adhesion molecules ( Metryka et al, 2018 ; Pollard et al, 2019 ; Hossein-Khannazer et al, 2020 ; Hu et al, 2020 ).
…”
Section: Introductionmentioning
confidence: 99%
“…This may result in decreased latency, viral reactivation, and apoptosis induction [71,72]. Indeed, both ATO and Lena treatments used as single agents are known to induce oxidative stress and ROS generation [52,73,74]. In multiple myeloma, Lena inhibited hydrogen peroxide decomposition, resulting in increased oxidative stress and cytotoxicity [73].…”
Section: Discussionmentioning
confidence: 99%
“…In multiple myeloma, Lena inhibited hydrogen peroxide decomposition, resulting in increased oxidative stress and cytotoxicity [73]. Furthermore, ROS accumulation in target cells is documented as one of the established mechanisms contributing to ATO cytotoxicity [74].…”
Section: Discussionmentioning
confidence: 99%